Implementasi Least Square Method Dalam Evaluasi Hasil Uprating Transformator Distribusi - Rachmat Sutjipto; Sungkowo, Heri; Khristiana , Harrij Mukti; Kharisma , Dhimas Dhesah; Galang Putra Fauzy; Faradina Agiesta Anjali (Elposys: Jurnal Sistem Kelistrikan, 2025)
Overloading in distribution transformers negatively affects operational reliability, efficiency, and equipment lifespan. At Gardu Distribusi C0058 PT PLN (Persero) ULP Bululawang, the transformer with a 160 kVA capacity exceeded the safe loading threshold of 80%, reaching 92.2% in the first semester of 2022 and 90.1% in the second semester of 2022. This study aimed to analyze the effectiveness of the uprating method as a solution to mitigate overloading issues while ensuring long-term transformer performance. The research employed quantitative analysis with direct measurement, load factor evaluation, and load forecasting using the Least Square method. Before the uprating process, the transformer experienced a peak load of 147.55 kVA (91.7%), significantly surpassing the recommended safety limits. The uprating process increased the transformer capacity from 160 kVA to 200 kVA, reducing the loading percentage to 73.57%, which brought it back within the acceptable operational range. Furthermore, load forecasting using the Least Square method predicted that the transformer would remain within a safe load level, reaching 79.73% in 2027, ensuring stability for the next five years. These findings align with previous studies emphasizing the effectiveness of transformer uprating as an alternative to relocation or additional transformer installation. However, further research is required to evaluate the impact on protective devices and system reliability. This study highlights the viability of uprating as an efficient and cost-effective strategy for managing transformer overloading in distribution networks.